Pemanfaatan Sumber Daya Alam sebagai Terapi Alternatif dalam Menurunkan Tekanan Darah pada Penderita Hipertensi: Systematic Review - Siagian, Heriviyatno J; Baeda, Abd. Gani; Alifariki, La Ode (NHM PRESS, 2025)
Despite the availability of effective pharmacological treatments, blood pressure control remains suboptimal due to medication-related side effects, adherence issues, and limited access to healthcare, especially in low- and middle-income countries. This systematic review aims to evaluate the efficacy and safety of natural resources in reducing blood pressure among individuals with hypertension, based on evidence from randomized controlled trials (RCTs). Following the PRISMA 2020 guidelines, a comprehensive literature search was conducted in PubMed, ScienceDirect, Cochrane Library, and Medline. Eligible studies were English-language RCTs investigating the effects of medicinal plants, herbal extracts, or natural dietary supplements on systolic and/or diastolic blood pressure. Data were extracted on study design, population characteristics, type of intervention, duration, outcomes, and safety. Twenty-four RCTs were included, covering interventions such as Hibiscus sabdariffa, Nigella sativa, aged garlic extract, oat bran, celery, and polyherbal formulations. Most interventions showed significant reductions in blood pressure, especially in individuals with stage 1 hypertension. Side effects were rare and mild. Conclusion: Natural resources show promise as adjunct antihypertensive therapies, but study heterogeneity limits generalizability. Standardized, large-scale trials are needed.